Rapid Identification of the Receptor‐Binding Specificity of Influenza A Viruses by Fluorogenic Glycofoldamers. Issue 45 (11th August 2016) - He, Xiao‐Peng; Zeng, Ya‐Li; Tang, Xin‐Ying; Li, Na; Zhou, Dong‐Ming; Chen, Guo‐Rong; Tian, He
Abstract: The re‐emergence of influenza raises a global concern that viral pandemics can unpredictably occur. However, effective approaches that can probe the infection risk of influenza viruses for humans are rare. In this work, we develop a glycofoldamer that can rapidly identify the glycan‐receptor specificity of influenza viruses in a high‐throughput manner. The coupling of glycan receptors that can be recognized by hemagglutinin (a surface protein on the virion capsid of influenza) to a fluorogenic‐dye foldamer produces the glycofoldamers with minimal fluorescence in aqueous solution. After interaction with human‐infecting virus strains for only five minutes, the fluorescence intensity of the glycofoldamer is remarkably enhanced with a blue‐shifted emission peak. The probes have also proven effective for the rapid identification of 1) the human‐ or bird‐infecting properties of influenza viruses in a high‐throughput manner and 2) the receptor‐specificity switch of a virus strain by mutations. Abstract : Glycofoldamers : The coupling of sialylglycans to a unique dye foldamer produces glycofoldamers that can rapidly identify the human‐ or avian‐infecting properties of influenza viruses in a high‐throughput screening. The mutation‐induced receptor‐specificity switch of a virus was also identified with this approach.